Calidad percibida en los servicios de salud que presta el Subcentro 001074, a la población urbana del Cantón Sozoranga, período 2017 - Guerrero Saavedra, Adriana de Lourdes (2019)
The objective of the work presented below is to establish the perceived quality of the health services provided by Subcentro 001074 in the urban area of the Sozoranga canton during the year 2017. The research comes from a mixed design (qualitative and quantitative), in the qualitative through the observation was closely observed what related to the provision of health services; as well as having an overview of the physical state of the facilities that is regular, because it lacks a good infrastructure with good facilities and medical equipment, and quantitatively, a survey was conducted on a population sample of users, to determine the perception of the quality of health services provided by the Subcentro Regarding the most relevant result according to the specific objectives to comply with the general objective, it determines that there is a deficient quality of the services provided by the Subcentro de Salud, which is expressed at a level -1,77.